Inactivation of polyphenol oxidase and peroxidase activity in mangosteen pericarp via blanching: correlation between anthocyanins and enzyme activities - Ijod, Giroon; Mohamed Nawawi, Nur Izzati; Sulaiman, Rabiha; Khalid, Nurul Izzah; Anwar, Farooq; Mohd Adzahan, Noranizan; Mohamad Azman, Ezzat (Oxford University Press, 2025)
Mangosteen pericarp (MP), rich in polyphenols and antioxidants, is often discarded as agro-waste. Its anthocyanins (ACNs), potential natural colourants, are compromised by high polyphenol oxidase (PPO) and peroxidase (POD) activity. This study examined the effects of hot water and steam blanching on PPO and POD inactivation in MP. Blanching for 0, 30, 60, 90 and 120 s at 100°C. Hot water inactivated 89.57% PPO (t1/2 = ~67 s) and 92.13% POD (t1/2 = ~33.6 s), while steam inactivated 52.81% PPO (t1/2 = ~113.7 s) and 97.07% POD (t1/2 = ~61.8 s). Despite better enzyme inactivation with hot water, it adversely affected ACNs stability. Steam blanching for 90 s, as determined by principal component analysis (PCA), preserved the highest ACNs, phenolics, and antioxidant activities. Cyanidin-3-O-sophoroside (C3S) and cyanidin-3-O-glucoside (C3G) were identified via LCMS and HPLC, offering insights for preserving ACNs as natural colourants.